CORRELATION BETWEEN COMPRESSIVE AND TENSILE SPLITTING STRENGTH OF GEOPOLYMER FIBER CONCRETE (Jurnal Teknologi (Sciences & Engineering), 2024)
Geopolymer concrete mixture contain fine and coarse aggregate, fly ash and activator, composed from sodium silicate and sodium hydroxide. Like normal concrete, geopolymer concrete is weak in terms of tensile strength, so fiber needs to be added to improve the mechanical properties of geopolymer concrete. In this research nylon and steel fiber are added to the geopolymer concrete mixture, with percentage from 0.5%, 0.75%, 1%, 1.5% and 2% of volume. The correlation between compressive and tensile splitting strength of geopolymer steel and nylon fiber concrete were evaluated in this research program. The relationship between tensile splitting strength and compressive strength of geopolymer concrete will be built in a mathematical model using multivariable non-linear regression from SPSS software. The specimens are cylindrical concrete, which have diameter of 100 mm and height of 200 mm. The specimen undergo a curing process in an oven at 60oC for duration of 24 hour. Geopolymer concrete mixture with a fiber percentage of 0.75% have a good workability, since they still meet the slump value requirements (10 + 2 cm). The compressive strength reaches the highest value at 0.75%, for both steel and nylon fibers. The addition of up to 2% steel fiber produces a splitting tensile strength 12.06% higher than geopolymer concrete with nylon fiber. The equation model proposed for geopolymer fiber concrete is fspt = 0.049f'c.exp(0.7p), with the R-square values from 0.722 - 0.715.